A comprehensive approach for the selection of a portfolio of interdependent projects. An application to subsidized projects in Spain. (April 2018) - Alvarez-García, B.; Fernández-Castro, A.S.
Highlights: A fuzzy multi-objective interactive model to select project portfolios is presented. Special attention is paid to the dependencies existing among the projects. The model is a comprehensive and flexible tool designed from a realistic point of view. The model exploits the expertise of individuals who can express their opinions in a subjective way. The model is applied to a large set of projects aimed at the development of coal mining areas in Galicia (Spain). Abstract: Interdependency is an ubiquitous concept in project portfolio selection, both at the firm and industry levels. However, despite the wide acceptance of this fact, there is a remarkable scarcity of models involving interdependencies amongst non-financial investments. This paper presents a flexible model developed to address the scarcity of interdependency models: a fuzzy interactive multi-objective model, based on the reference point approach, which elicits the evaluation of interdependencies from a group of experts in a natural way. The model is presented in a sequential way, to highlight its contributions. Then, it is applied to solve a real portfolio selection problem, consisting on a large set of investment projects eligible for a subsidy program. The portfolio selected using the model achieves a sharp reduction in the deviations from objectives compared to the portfolio originally selected by the granting authorities.